The book of Micah - Nogalski, James (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2024)
"An evangelical commentary on the book of Micah"--
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; RELIGION / Biblical Commentary / Old Testament / Prophets; RELIGION / Biblical Studies / Old Testament / Prophets; Commentaries